Investigating the Relationship Between Midazolam Serum Concentrations and Paediatric Delirium in Critically Ill Children - Sabrina Marongiu; Mathieu S. Bolhuis; Daan J. Touw; Martin C. J. Kneyber (Pediatric Reports, 2025)
Objectives: Intravenous midazolam is widely used for sedation in critically ill children. Sometimes, these children develop a paediatric delirium (PD). Our aim was to determine the relationship between midazolam serum concentration and the development of new PD in critically ill children. Design: Prospective observational pilot study. Setting: Paediatric Intensive Care Unit (PICU), Groningen, the Netherlands. Patients: All children admitted to the PICU from October–December 2019 who received continuous midazolam administration. Interventions: None. Measurements and main results: Twenty-five percent (n = 7) of the included patients (n = 28) developed new PD. In most patients, PD occurred following midazolam dose reduction. The median cumulative midazolam dose was higher in patients who developed PD compared to those without PD. We analysed 104 blood samples to determine the midazolam concentrations. To determine whether patients had PD, the Sophia Observation withdrawal Symptoms-Paediatric Delirium (SOS-PD) score was used. Patients suffering PD (n = 7) had a lower median midazolam concentration on that day compared with the day prior to PD detection. Analysis of the active metabolites, 1-hydroxymidazolam and 1-hydroxymidazolam glucuronide, showed similar results. Conclusions: PD may be linked to a sudden and significant reduction in the midazolam concentration in critically ill children. Further investigation in larger patient populations is necessary to validate our findings.